Legal Problems Using AstraZeneca Vaccine: Hermeneutic Analysis of the Fatwa of the Indonesian Ulema Council - Sa'diyah, Miftahus; Masuwd, Mowafg Abrahem; Supandi, Ach. Faqih (Journal of Islamic Law, 2022)
Recently, the Indonesian Muslim community has been shocked by the government's policy to use the AstraZeneca Vaccine to minimize the negative impact of Corona Virus Disease 10 (Covid-19). This policy is permitted by the Fatwa of the Indonesian Ulema Council (MUI), although it uses trypsin from pigs to make the vaccine. This article explains the legal problems of using the vaccine from a hermeneutic perspective. This research is a literature review using the MUI Fatwa Number 14 of 2021 concerning the Law on the Use of the Covid-19 Vaccine for AstraZeneca Products as primary data and analyzing it descriptively with a hermeneutic approach. The authors found that the MUI Fatwa Number 14 of 2021 was a direct request from the government and was used as a guideline for implementing the AstraZeneca Vaccine for Muslim communities in Indonesia. In determining the fatwa on the permissibility of using the AstraZeneca Vaccine in an emergency to create herd immunity against Covid-19, the MUI Fatwa Commission uses the qiyās and maqāsid al-syarī’ah methods. The use of these two methods can be seen from the citation of several fiqh rules and opinions of previous scholars. Even though there are contradictory responses to the MUI Fatwa, the only difference lies in the concept of istihālah (change of unclean objects to become holy) used by the fatwa institution.